Accuracy of OMI ECG findings versus STEMI criteria for diagnosis of acute coronary occlusion myocardial infarction. (April 2021) - Pendell Meyers, H.; Bracey, Alexander; Lee, Daniel; Lichtenheld, Andrew; Li, Wei J.; Singer, Daniel D.; Rollins, Zach; Kane, Jesse A.; Dodd, Kenneth W.; Meyers, Kristen E.; Shroff, Gautam R.; Singer, Adam J.; et al.
Highlights: Acute coronary occlusions without ST elevation criteria suffer double mortality without reperfusion. ECG findings other than ST elevation criteria can identify occlusion myocardial infarction sooner and more accurately. Our results justify further research to evaluate the external validity of advanced ECG interpretation. Abstract: Objective: In the STEMI paradigm of Acute Myocardial Infarction (AMI), many NSTEMI patients have unrecognized acute coronary occlusion MI (OMI), may not receive emergent reperfusion, and have higher mortality than NSTEMI patients without occlusion. We have proposed a new OMI vs. Non-Occlusion MI (NOMI) paradigm shift. We sought to compare the diagnostic accuracy of OMI ECG findings vs. formal STEMI criteria for the diagnosis of OMI. We hypothesized that blinded interpretation for predefined OMI ECG findings would be more accurate than STEMI criteria for the diagnosis of OMI. Methods: We performed a retrospective case-control study of patients with suspected acute coronary syndrome. The primary definition of OMI was either 1) acute TIMI 0–2 flow culprit or 2) TIMI 3 flow culprit with peak troponin T ≥ 1.0 ng/mL or I ≥ 10.0 ng/mL. Results: 808 patients were included, of whom 49% had AMI (33% OMI; 16% NOMI). Sensitivity, specificity, and accuracy of STEMI criteria vs Interpreter 1 using OMI ECG findings among 808 patients were 41% vs 86%, 94% vs 91%, and 77% vs 89%, and for Interpreter 2 among 250 patients were 36% vs 80%, 91% vs 92%, and 76% vs 89%. STEMI(−) OMI patients had similar infarct size and mortality as STEMI(+) OMI patients, but greater delays to angiography. Conclusions: Blinded interpretation using predefined OMI ECG findings was superior to STEMI criteria for the ECG diagnosis of Occlusion MI. These data support further investigation into the OMI vs. NOMI paradigm and suggest that STEMI(−) OMI patients could be identified rapidly and noninvasively for emergent reperfusion using more accurate ECG interpretation.